Conservatism : an invitation to the great tradition - Scruton, Roger (New York : All points books, 2017)
A brief magisterial introduction to the conservative tradition by one of Britain's leading intellectuals. In Conservatism, Roger Scruton offers the reader an invitation into the world of political philosophy by explaining the history and evolution of the conservative movement over the centuries. With the clarity and authority of a gifted teacher, he discusses the ideology's perspective on civil society, the rule of law, freedom, morality, property, rights, and the role of the state. In a time when many claim that conservatives lack a unified intellectual belief system, this book makes a very strong case to the contrary, one that politically-minded readers will find compelling and refreshing. Scruton analyzes the origins and development of conservatism through the philosophies and thoughts of John Locke, Thomas Hobbes, Adam Smith and Milton Friedman, among others. He shows how conservative ideas have influenced the political sector through the careers of a diverse cast of politicians, such as Thomas Jefferson, Benjamin Disraeli, Ronald Reagan and Margaret Thatcher. He also takes a close look at the changing relationship between conservative politics, capitalism, and free markets in both the UK and the US. This clear, incisive guide is essential reading for anyone wishing to understand Western politics and policies, now and over the last three centuries
Pre-history -- The birth of philosophical conservatism -- Conservatism in Germany and France -- Cultural conservatism -- The impact of socialism -- Conservatism now
Reprint. Originally published: London : Profile Books, 2017
Includes bibliographical references (pages 157-164)
Keywords: Conservatism